Biosynthesis of Zinc Oxide Nanoparticles by Sol-gel Approach: Enhancing Anticorrosion Efficacy - Ojochenemi Nora Unuata; Oluwatosin Kudirat Shittu; Jimoh Oladejo Tijani; Hassan Abdulsalam Adewuyi (Pharmaceutical and Biomedical Research)
Background: Corrosion is a pervasive issue affecting various industries, resulting in significant economic losses. Traditional corrosion protection methods often involve toxic chemicals, prompting the need for eco-friendly alternatives. This study demonstrates the green synthesis of zinc oxide (ZnO) nanoparticles via a sol-gel approach and their integration into epoxy resin coating to enhance anticorrosion efficacy. Objectives: This study aims to synthesize ZnO nanoparticles using a green synthesis method, characterize their properties, and evaluate their potential applications in corrosion protection and biomedical fields. Methods: The synthesized nanoparticles were characterized using x-ray diffraction (XRD), energy dispersive spectroscopy (EDS), and high-resolution transmission electron microscopy (HRTEM). The ZnO nanoparticles were then integrated into epoxy resin to develop a nano-coating optimized for enhanced performance. Results: The XRD analysis revealed the formation of a spherical zincite ZnO phase with an average crystallite size of 16.7 nm. HRTEM confirmed the average particle size of 16.3 nm, with uniform morphology. Electrochemical impedance spectroscopy (EIS) analysis demonstrated the exceptional corrosion resistance of the ZnO/epoxy resin coating. The green synthesis method produced uniform ZnO nanoparticles successfully integrated into the epoxy resin coating. The resulting nano-coating exhibited enhanced corrosion resistance, making it a promising solution for protecting metal surfaces. Conclusion: This study demonstrates the green synthesis of ZnO nanoparticles using a sol-gel approach. The synthesized nanoparticles were characterized using XRD, EDS, and HRTEM. The ZnO nanoparticles were then integrated into epoxy resin to develop a nano-coating optimized for enhanced corrosion resistance. The results show that the ZnO/epoxy resin coating exhibits exceptional corrosion resistance, making it a promising solution for protecting metal surfaces.